Algoritmo genético aplicado no controle de posição do rotor de um motor de corrente contínua com rejeição a distúrbios por ação feedforward - Guimarães, Ádller de Oliveira (2013)
The versatility of direct current machines combined with the relative simplicity of their drive systems ensures its continued use in a wide variety of applications in industrial electrical systems, more specifically in applications that requiring a wide range of speed and position control of the rotor. In this work, a new method for tuning Proportional-Integral-Derivative (PID) controllers with disturbance rejection using Genetic Algorithm (GA) is proposed. The proportional, integral and derivative gains, designed to control the rotor position of DC motor are optimized using GA in group with Ziegler - Nichols technique, and the rejection of disturbances is obtained from the implementation of feedforward control in the algorithm. Preliminary results show that the proposed GA gave a satisfactory response, both in transitional regime as at steady state, and shows good performance in disturbance rejection. To validate this technique, the results obtained were compared with other methods in literature